Laurenskerk as public space (Bulletin KNOB, 2011)
In this article the exhibition 'A monument full of stories' in Laurenskerk, realized by design office Kossmann.de jong in 2010, is considered within the context of the current function of cultural heritage in a society that is getting more and more divided in a process of individualization and demarcation. Possibly, cultural heritage can play a part in the fragmented city as public space, as a platform of civil society. Since the seventies historical and community museums have focused on showing the everyday culture of minorities and disadvantaged groups. Showing their own culture was considered a form of emancipation and empowerment. As at this juncture relations between various groups are becoming increasingly antagonistic and culture is regarded as the cause of desirable or undesirable social conduct, one may wonder whether the task of heritage institutions should particularly be oriented towards a country's characteristics. The direct environment of Laurenskerk has changed considerably, first through the Reconstruction and subsequently through large-scale high-rise building and spectacular architecture. Laurenskerk is surrounded by 'no place' and 'junk space'. As a consequence, the special form and thus the significance of the church as the sole relic of medieval Rotterdam has become indecipherable. Sprucing up public space around the church and making its interior more attractive fit in with the current vision of the city, notably the city centre.City centres are considered high-quality accommodation spaces, in which cultural consumption and leisure are most important. Due to the expansion of activities Laurenskerk, too, has become part of commercial and cultural supply. The exhibition links up with the expectations of the visitors, who want to be invited - not addressed - in order to be absorbed in the past and consequently, in the meaning of Laurenskerk. At the exhibition a variety of media are put in to show and tell the story of the church from various perspectives. As a result, the visitor has the sensation of being close to the historical developments. In this sense this presentation is a good example of media attention and virtualization of heritage presentations, whereby authenticity is not so much to be found in the objects themselves as in the experience of them. As Laurenskerk itself is also largely a reconstruction due to the bombing of 1940, this choice was obvious. But the exhibition also goes one step further. The story of Laurenskerk may serve to make visitors think about the religious traditions connected with the building. 'Time' and 'place' have a special significance in Laurenskerk; here it is only memory that preserves the past. Because of the connection made at the exhibition between the experience of heritage, the value of remembrance, and the foundations of human actions, this exhibition is a good example of the ethical turn in heritage presentations. The emphasis is on what connects people, not primarily on historical facts or identities. Heritage institutions, and in particular monuments, may function in public space as cosmopolitan canopies, places where people from different origin gather peacefully for all sorts of activities.